Communication between gut microbiota-derived metabolites and the tumor microenvironment - Hu, Xinyi; Li, Bo; Li, Yuanqing; Liang, Yushan; Huang, Tingting (Frontiers in Immunology, 2025)
The gut microbiota has been increasingly recognized as a critical player in maintaining human health and influencing disease development. The tumor microenvironment (TME) is pivotal in tumor development and progression, comprising immune cells, stromal elements, extracellular matrix components, and cytokines. Recent studies have highlighted the promising potential of gut microbiota-derived metabolites (e.g., short-chain fatty acids, bile acids, polyamines, and tryptophan derivatives) to reshape the TME in various ways, generating significant interest for the development of novel therapeutic strategies. Beyond their established effects on traditional cancer treatments, emerging evidence suggests that microbiome-based interventions can substantially enhance cancer immunotherapy. However, the variable role of gut microbiota in modulating therapeutic responses complicates the prediction of clinical outcomes. Therefore, understanding the crosstalk between the gut microbiota and the TME is crucial and holds promise for the development of personalized and comprehensive cancer management strategies. This review aims to summarize the reciprocal regulatory mechanisms between gut microbiota-derived metabolites and the TME, and to explore how these interactions can be leveraged to improve cancer immunotherapy.